Spatially resolved transcriptomics: a comprehensive review of their technological advances, applications, and challenges - Cheng, Mengnan; Jiang, Yujia; Xu, Jiangshan; Mentis, Alexios-Fotios A.; Wang, Shuai; Zheng, Huiwen; Sahu, Sunil Kumar; Liu, Longqi; Xu, Xun (Journal of genetics and genomics, 2023)
The ability to explore life kingdoms is largely driven by innovations and breakthroughs in technology, from the invention of the microscope 350 years ago to the recent emergence of single-cell sequencing, by which the scientific community has been able to visualize life at an unprecedented resolution. Most recently, the Spatially Resolved Transcriptomics (SRT) technologies have filled the gap in probing the spatial or even three-dimensional organization of the molecular foundation behind the molecular mysteries of life, including the origin of different cellular populations developed from totipotent cells and human diseases. In this review, we introduce recent progresses and challenges on SRT from the perspectives of technologies and bioinformatic tools, as well as the representative SRT applications. With the currently fast-moving progress of the SRT technologies and promising results from early adopted research projects, we can foresee the bright future of such new tools in understanding life at the most profound analytical level.